Scanned stripping chronopotentiometry at bismuth film rotating disc electrodes: a method for quantitative dynamic metal speciation - Pinheiro, Jose Paulo; Rocha, Luciana S.; Goveia, Danielle [UNESP]; Town, Raewyn M. (CSIRO Publishing, 2014)
Environmental contextElectroanalytical methods have found wide application in trace metal speciation analysis in environmental systems. The need to find functional alternatives to mercury electrodes for in situ speciation studies has encouraged the use of bismuth as a solid-state electrode substrate. We demonstrate the utility of bismuth electrodes for quantitative dynamic speciation analysis.Bismuth film electrodes are employed for dynamic metal speciation analysis of Pb-II complexes by stripping chronopotentiometry at scanned deposition potential (SSCP). Their performance is found to be comparable to that of mercury-film electrodes. The quantitative SSCP expressions that describe the thermodynamic and kinetic complexation parameters are straightforwardly applicable to this solid electrode.
Keywords: Bi film electrode, citric acid, dynamic metal speciation, iminodiacetic acid, lability, thin Hg film electrode.